Peran Kepala Sekolah dalam Meningkatan Manajemen dan Mutu Pendidikan SD Kecamatan Dawe - Sudarti Sudarti; Achmad Hilal Madjdi; Susanti Susanti (ILUMINASI: Journal of Research in Education, 2023)
Based on actual observations, there has not been much research explaining the role of school principals in improving the management and quality of education.Meanwhile, research on the role of school principals in improving the management and quality of education is important. Based on these observations, research will be carried out on the role of school principals in improving the quality of education. This research method applies qualitative methods and types of literature studies.. The role of the principal in improving the quality of education is that the principal acts as a manager, the principal acts as an administrator, the principal acts as a supervisorr, the principal acts as an educator, and the principal acts as anentrepreneur.